Based on the length of the tilter wing of combined machine body preparation for potato planting (Texas Journal of Agriculture and Biological Sciences, 2022)
The article presents the results of experimental studies on the influence of the length of the tipper wing of the machine body that prepares the soil for planting potatoes on the agrotechnical and energetic performance of the device. The hulls are based on the length of the flipper wing